Characteristics of shear waves in shallow seafloor sediment in the Middle Southern Yellow Sea. Issue 4 (24th March 2022) - Sun, Zhiwen; Kan, Guangming; Wang, Jingqiang; Jia, Yonggang; Meng, Xiangmei; Li, Guanbao; Pei, Yanliang
Abstract: The shear wave characteristics of shallow seafloor sediment are vital to marine acoustic study and ocean engineering exploration. We analyzed the shear wave speed and the physical properties of the southern Yellow Sea sediment based on the Grain-Shearing (GS) model. The results show that: (1) The shear wave speed of the high-porosity sediment is lower than that of the low-porosity sediment; (2) The shear wave speed of the fine-grained sediment is lower than that of the coarse-grained sediment; (3) The burial depth of the sediment has a significant influence on the shear wave speed of the seafloor sediment. The GS model agrees well with the measurement data from the southern Yellow Sea. However, the quantitative analysis of the impact of input parameters on the GS model requires further research.